The Impact of Guided Inquiry Learning Model Using Virtual Phet Experiment Method on Students' Critical Thinking Skills (Universitas PGRI Sumatera Barat, 2022)
The purpose of this study was to determine whether the use of the guided inquiry learning model with the Phet virtual experiment method had more effect on the critical thinking skills of students at SMA N 1 Kalasan compared to conventional learning models. This type of research is a quasi-experimental using an experimental class that uses a guided inquiry learning model and a control class that uses a conventional learning model. Data was collected by conducting pretest and posttest on students' critical thinking skills in both classes. Data analysis was performed using MANOVA analysis. The results showed that the use of the guided inquiry learning model with the Phet virtual experiment method had more effect on students' critical thinking skills than the use of conventional learning models.